Analysis of Earthquake Vulnerability of The Demak Coastal Area based on the HVSR (Horizontal To Vertical Spectral Ratio) Method - Muhammad Irham Nurwidyanto; Udi Harmoko; Rahmat Gernowo; Gregrius Alvin Fernando; Sorja Koesuma (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2024)
Most of the Demak Coastal area, especially on the north coast, has a subsurface structure which is quite thick sediment. The impact of an earthquake will cause damage to subsurface structures and buildings above it, so a method is needed that can determine earthquake vulnerability in an area to take mitigation steps. This research aims to analyze vulnerability to earthquakes based on natural frequency (fo), amplification (Ao) and seismic vulnerability index (SVI). The research was carried out by measuring the microseismic signal response at 89 locations using a 3-component seismograph and data logger. The research results showed that the dominant frequency varied from 0.26 – 5.26 Hz, the amplification factor varied from 0.51 – 3.56 and the seismic susceptibility index varied from 0.14-14.77 micro cm2/s. The study area was classified into low SVI (SVI < 5), medium SVI (5 < SVI < 10), and high SVI (SVI > 10).  The potential earthquake hazard described by SVI with a value range of 10 < SVI (high classification) is found at observation station 60 (Bedono Hamlet) and observation station 70 (Karangwaru Hamlet Cemetery)